Temporal and Spatial Patterns of Wind Erosion Climate Indices and Their Responses to Atmospheric and Oceanic Circulation Patterns in the Chinese Mollisol Region over the Past 61 Years - HU Wentao; ZHENG Fenli; GAO Xiaoyu; ZHENG Runhe; FU Jinxia; LI Zhi; ZHANG Jiaqiong (Shuitu Baochi Xuebao)
[Objective] A study on the spatial and temporal patterns of wind erosion climate indices and their responses to atmospheric and oceanic circulation patterns in the Chinese Mollisol region is of great significance for the early warning and prevention of wind erosion. [Methods] Four wind erosion climate indices, including occurrence frequency of ≥ 5 m/s of threshold wind of transporting sand, daily maximum wind velocity, daily extreme wind velocity and wind erosion climatic erosivity, were selected to address the spatial and temporal patterns of wind erosion climate indices in the spring (March-May) of the Chinese Mollisol region from 1960 to 2020 based on the daily wind speed data and meteorological data, and to elucidate the impacts of atmospheric and ocean circulation patterns on these indices. The research methods included the moving average, Mann-Kendall test and multiple wavelet coherence. [Results] The occurrence frequency of ≥ 5 m/s threshold wind speed of transporting sand varied from 5 to 30 times per season, daily maximum wind velocity varied from 6.1 to 8.7 m/s, daily extreme wind velocity varied from 9.8 to 12.2 m/s, and wind erosion climatic erosivity varied from 19.5 to 101.1 in the Chinese Mollisol region form 1960 to 2020. An intermonthly change trend of these four wind erosion climate indices followed by April > May > March. Except for daily extreme wind velocity, there was a significant decreasing trend of the other three indices from 1960 to 2020 with a significant abrupt change around 1990, but a noticeable upward trend of these indices was observed after 2014. The spatial distribution of wind erosion climate indices in the Chinese Mollisol region showed an increasing and then decreasing trend from the northwest to the southeast, and topography was a crucial factor affecting the distribution of wind erosion climate indices. Moreover, the Asia Polar Vortex Intensity Index (APVII) was the most important circulation pattern affecting wind erosion climate indices, and the Pacific/North American Pattern (PNA) also had a significant impact on wind erosion climate indices. However, there was no significant correlation between the wind erosion climate indices and the superposition of APVII and PNA, while the superpositions of three APVII-PNA-AO patterns had a significant effect on the occurrence frequency of the threshold wind of transporting sand. Overall, after 2014, there was a rapid increasing trend in the wind erosion climate indices in the Chinese Mollisol region, and both APVII and PNA circulation patterns had significant impacts on the wind erosion climate indices. [Conclusion] The factors that influenced the spatial and temporal patterns of wind erosion climate indices in the Chinese Mollisol region include wind velocity, topography and atmospheric-oceanic circulation patterns, etc. Attention should be paid to the potential wind erosion hazards caused by the enhancement of wind erosion dynamics after 2014.